1998
DOI: 10.1097/00005176-199805000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Ctla-4 Gene Polymorphism Is Associated With Predisposition to Coeliac Disease.

Abstract: Background-Susceptibility to coeliac disease is strongly associated with particular HLA class II alleles. However, non-HLA genetic factors are likely to be required for the development of the disease. Among candidate genes is the CTLA-4 (cytotoxic T lymphocyte associated) gene located on chromosome 2q33 in humans, which encodes a cell surface molecule providing a negative signal for T cell activation. Aims-To investigate CTLA-4 exon 1 polymorphism (position 49 A/G) in patients with coeliac disease. Patients-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 14 publications
4
62
0
3
Order By: Relevance
“…To date, there is no explanation for this heterogeneity in the age of CD onset, but one can hypothesize that different genes are involved in childhood and adulthood disease, as already described in relation to type 1/type 2 diabetes [26,27] and Graves' disease [19]. We tested this hypothesis by stratifying the 180 CD patients for age of disease-onset: 110 patients were diagnosed with CD before the age of 15 years (described in [28]), and 70 patients were diagnosed after the age of 18 years. As shown in Table 2, the effect of the R241-variant was more prominent in patients diagnosed in adulthood than in childhood-onset patients ( 2 for genotype distribution ϭ 25.7, p Ͻ 10 -4 for comparison between controls and adulthood patients; 2 ϭ 11.2, p ϭ 0.0037 for comparison between controls and childhood-onset patients).…”
Section: Resultsmentioning
confidence: 95%
“…To date, there is no explanation for this heterogeneity in the age of CD onset, but one can hypothesize that different genes are involved in childhood and adulthood disease, as already described in relation to type 1/type 2 diabetes [26,27] and Graves' disease [19]. We tested this hypothesis by stratifying the 180 CD patients for age of disease-onset: 110 patients were diagnosed with CD before the age of 15 years (described in [28]), and 70 patients were diagnosed after the age of 18 years. As shown in Table 2, the effect of the R241-variant was more prominent in patients diagnosed in adulthood than in childhood-onset patients ( 2 for genotype distribution ϭ 25.7, p Ͻ 10 -4 for comparison between controls and adulthood patients; 2 ϭ 11.2, p ϭ 0.0037 for comparison between controls and childhood-onset patients).…”
Section: Resultsmentioning
confidence: 95%
“…This region harbors CD28 and CTLA-4, genes that are thought to play an important role in regulating lymphocyte proliferation. Furthermore, numerous functional and association studies have suggested that CTLA-4 may also confer susceptibility to psoriasis and celiac disease (42,43). Thus, collective evidence suggests the presence of a gene (or closely mapped genes) that may cause a primary defect in regulation of immune responses, creating an underlying predisposition to development of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…60 The T-lymphocyte regulatory genes CD28, CTLA4 and ICOS are found in a 300 kb block of chromosome 2q33. Much is now known regarding their immunological function: engagement of CD28 on naïve T cells by CD80/CD86 (B7) ligands on antigen presenting cells provides a potent co-stimulatory signal to T cells activated through their T cell receptor; engagement of ICOS on T cells by ICOS ligand (B7-H2) also provides a positive proliferative and cytokine secretion signal, although cell surface ICOS is expressed on activated rather than naïve T cells suggesting a later regulatory function; cell surface CTLA4 is also upregulated on T cell activation, has a higher affinity for its CD80/86 ligands than CD28, and provides a negative signal to regulate T cell activation.…”
Section: Cd28-ctla4-icos Variants (2q33)mentioning
confidence: 99%